Optimising default radiographic exposure factors using Deviation Index. Issue 4 (November 2020) - Creeden, A.; Curtis, M.
Abstract: Introduction: Radiographers have a duty to ensure that radiation doses to patients are as low as reasonably achievable . With digital technologies, exposure factors which achieve the optimum balance between image noise and patient dose must be sought. In digital radiography, Deviation Index (DI) values provide the radiographer with feedback on the appropriateness of individual exposures but can also be tracked as part of a departmental quality assurance programme. Methods: In November 2017, exposure logs were extracted from six digital radiography (DR) x-ray systems, collated and analysed. Five examinations were identified which frequently produced DI values outside the manufacturer's recommended Optimal Range ( -3 to + 2 ). Incremental improvements were made to the default exposure settings for these examinations via a cyclical process of modification and re-evaluation. A full data collection exercise was then repeated in April 2019. Results: At baseline, 10, 658 out of 29, 637 (36.0%) exposures had DI values outside the manufacturer's recommended Optimal Range, but for some individual examinations the proportion was as high as 547 out of 725 (74.5%). Following multiple optimisation cycles, the overall proportion of examinations outside the Optimal Range had fallen to 7611 out of 26, 759 (28.4%). Default milliampere-seconds (mAs) values for these examinations were reduced by between 22% and 50%. Conclusion: A marked reduction in patient doses can be achieved through a departmental programme of DI value monitoring and targeted optimisation of default exposure settings. Implications for practice: DI values should be routinely monitored as part of routine quality assurance programmes. Radiographers have a responsibility to ensure that they possess a clear understanding of DI values and that appropriate exposure settings are selected for each individual patient.